Consensus building on mathematics teacher readiness: A study using the modified nominal group technique. - Abu Talib, Sharida; Mohamad Nasri, Nurfaradilla; Mahmud, Muhammad Sofwan (Journal of Islamic, Social, Economics and Development, 2025)
This study was conducted to achieve expert consensus on a model of mathematics teachers' readiness as agents of change, which integrates professional knowledge and pedagogical skills. The Modified Nominal Group Technique (MNGT) was employed to evaluate the usability of the developed model. Mathematics teachers play a critical role in implementing educational reforms and therefore require guidance to ensure their readiness in meeting the demands of contemporary educational changes. However, previous studies have highlighted significant gaps in teacher readiness, particularly in linking professional expertise with more innovative teaching methods. Thus, this study utilized MNGT to ensure that the developed model meets suitability criteria based on systematic consensus. To evaluate its suitability and user satisfaction, 16 implementing experts were involved in workshop sessions. These experts were selected based on their service experience and backgrounds in mathematics. The evaluation results revealed that all the implementing experts agreed that the developed model is suitable and comprehensive as a guide for mathematics teachers. They also believed that the model is highly practical for application in classrooms, as its content encompasses critical aspects that teachers should address to conduct more effective teaching processes. The findings of this study are significant as a pragmatic framework for developing teacher professional programs and formulating policies to enhance the readiness of mathematics teachers in facing change. Further studies are recommended to assess and refine the proposed model across various educational settings.